The Effect of Trading Volume, Frequency and Market Capitalization on Stock Return of Chemical Sub Sector - Nurhayati, Immas (Jurnal Manajemen, 2022)
The purpose of this study was to analyze the impact of trading volume, trading frequency, and market capitalization on stock returns of the chemical sub-sector. This study uses quantitative data. The relationship between trading volume, trading frequency, and market capitalization with stock returns will be tested using single linear regression analysis, multiple linear regression analysis, correlation coefficient, coefficient of determination, autocorrelation, multicollinearity, heteroskedasticity, t-test, and F test. The independent variables in this study are trading volume, trading frequency, and market capitalization and the dependent variable is stock returns. The relationship between trading volume, trading frequency, market capitalization and stock returns can be written in the following multiple regression equation: Y = 0,123+ 0,866 X1 + 0,000 X2 + 0,000086 X3. Based on a simple regression test, all independent variables have a significant effect on the dependent variables, but using a multiple regression test, no one of all independent variables significantly affects the dependent variable. Based on the F test which significance value of 0.008 < 0.05, can conclude that variables trading volume, trading frequency, and market capitalization simultaneously have significant effect on stock returns. The coefficient of determination of 0,311 showed that the three independent variables have a contribution value of 31.1%, which means that trading volume, trading frequency, and market capitalization affect stock returns by 31.1%, and the remaining 68.9% is influenced by other factors that are not described in this study.